2004
DOI: 10.1002/14651858.cd003710.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Dual chamber versus single chamber ventricular pacemakers for sick sinus syndrome and atrioventricular block

Abstract: This review shows a trend towards greater effectiveness with dual chamber pacing compared to single chamber ventricular pacing, which supports the current British Pacing and Electrophysiology Group's Guidelines regarding atrioventricular block. Additional randomised controlled trial evidence from ongoing trials in this area will further inform the debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 179 publications
1
34
0
9
Order By: Relevance
“…Previous studies, including a meta-analysis of patients with SND and AV block, reported a significant reduction in pacemaker syndrome with dual-chamber pacing compared to single-chamber ventricular pacing (see Recommendations Table 1 and Table 3) (33,34,(67)(68)(69)(70)(71)(72)(73)(74). However, as indicated previously, crossover to dual-chamber pacing is heavily influenced by whether this can be accomplished by reprogramming alone in the presence of a dual-chamber pacemaker or by a surgical intervention.…”
Section: Pacemaker Syndromementioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies, including a meta-analysis of patients with SND and AV block, reported a significant reduction in pacemaker syndrome with dual-chamber pacing compared to single-chamber ventricular pacing (see Recommendations Table 1 and Table 3) (33,34,(67)(68)(69)(70)(71)(72)(73)(74). However, as indicated previously, crossover to dual-chamber pacing is heavily influenced by whether this can be accomplished by reprogramming alone in the presence of a dual-chamber pacemaker or by a surgical intervention.…”
Section: Pacemaker Syndromementioning
confidence: 88%
“…Of the 996 patients randomized to VVIR pacing, 182 (18.3%) developed severe pacemaker syndrome during follow-up that improved with reprogramming the device to DDDR pacing (33). A systematic review of the literature conducted by the Cochrane Collaboration reported a significant reduction in the symptoms of pacemaker syndrome associated with the use of dual-chamber pacing, compared to ventricular pacing, for both parallel and crossover design studies (34). A limitation of this analysis is the inclusion of patients with both SND and AV block indications for pacing.…”
Section: Pacemaker Syndromementioning
confidence: 99%
“…We chose dual chamber epicardial pacemaker because of coexistence of noncompacted myocardium of both ventricles and sick sinus syndrome. It has been reported that in sick sinus syndrome, more favorable results were obtained with dual chamber ventricular pacing (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados mostraron que en los datos de los GP no existe preferencia estadísticamente significativa por el marcapaseo "fisiológico" para la prevención de accidente cerebrovascular, insuficiencia cardiaca o muerte (OR 0,94; 95% IC: 0,80 -1,12), y sí encontró beneficio en la prevención de FA (OR 0,79; 95% IC: 0,68 -0,93) (14).…”
unclassified
“…Los ensayos TRC, mostraron en forma significativa resultados favorables en la capacidad de ejercicio (SMD -0,24; 95% CI -0,03 a -0,45) en los pacientes con marcapaso dual (14).…”
unclassified